Philodryas trilineata - Di Pietro, Diego Omar (2016)
Herpetological Collection of Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”, Buenos Aires, Argentina (MACN 48217, 12883–12886, 12893– 12896, 12898). This species is endemic to Argentina (provinces of Catamarca, Chubut, Córdoba, La Pampa, La Rioja, Mendoza, Neuquén, Río Negro, Salta, San Juan, San Luis and Tucumán) mainly in the Monte phytogeographic region (Leynaud and Bucher 1999. Misc. Publ. Acad. Nac. Sci. Córdoba 98:1–52; Giraudo and Scrocchi 2002. Smithson. Herpetol. Inform. Serv. 132:1–53; Giraudo et al. 2012. Cuad. Herpetol. 26:303–326).